2019
DOI: 10.1515/hf-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

A molecular model for reversible and irreversible hygroscopicity changes by thermal wood modification

Abstract: Heat treatment (HT) is a well-known means to reduce the equilibrium wood moisture content (EMC) at a specified relative humidity (RH). EMC is profoundly decreased by the loss of accessible hydroxyl groups (OH acc ) in the wood matrix by thermochemical reactions. However, the obtained EMC reduction after HT can be partly reversible, depending on the ability of the wood matrix polymers to fully mechanically relax during HT. We discuss the results of our earlier experimental study on the OH acc content and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Some studies explained that cross-linking reactions during Dry-HT enhance the cell wall matrix stiffness and restrict the expansion of the polymers to accommodate water molecules [30,31,43]. Other studies speculated that changes in the conformation of the matrix polymers hinder the relaxation of the cell wall polymers toward their thermodynamically most favorable arrangement [31,37,44]. Similar to the reduction in wood MC, the present study also showed differences in the change in tensile properties by the two HT techniques.…”
Section: Discussionsupporting
confidence: 68%
“…Some studies explained that cross-linking reactions during Dry-HT enhance the cell wall matrix stiffness and restrict the expansion of the polymers to accommodate water molecules [30,31,43]. Other studies speculated that changes in the conformation of the matrix polymers hinder the relaxation of the cell wall polymers toward their thermodynamically most favorable arrangement [31,37,44]. Similar to the reduction in wood MC, the present study also showed differences in the change in tensile properties by the two HT techniques.…”
Section: Discussionsupporting
confidence: 68%
“…If linked to impermanent H-bonding networks, this suggests that measurements of accessible OH content using D 2 O would change before and after the water-soaking stage. But this has not been observed [135]. The loss of mobile cell wall components during thermal modification will result in a cell wall that is in a higher energy stressed state under HT dry conditions, which can then relax when subsequently exposed to higher levels of moisture.…”
Section: Changes In Physical Propertiesmentioning
confidence: 98%
“…There are still possible sources of error arising from the estimation of dry mass within the DVS [134], and although the HDX experiments using a modified protocol produced results with repeatable results, a higher drying temperature in the DVS in order to measure the dry weight was found to produce an increase in accessible OH content by ? 0.5 mmol OH groups per gram of dry wood mass [135]. Further development is apparently required to produce reliably accurate OH accessibility data using a DVS apparatus in HDX experiments, but this remains a very convenient method for determination of accessible OH groups once reliability can be established.…”
Section: Hydroxyl (Oh) Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the amount of absorbed water can change independently from the OH accessibility (Stevens and Smith 1970;Rautkari et al 2013;Salmén and Stevanic 2018). There is evidence that additional factors have a strong impact on the amount of absorbed water without affecting the sorption site density, such as the degree of crosslinking in heat-treated wood (Altgen et al 2018;Willems et al 2020) or the spatial availability of wood cell walls in modified wood (Thybring et al 2020;Altgen et al 2020). Furthermore, Lindh et al (2016) showed that OH(3) groups in cellulose that are associated with the C(3) atom of the glucose units are unreactive to H-D exchange, but these OH groups may still form hydrogen bonds with water molecules.…”
Section: Introductionmentioning
confidence: 99%